Association of neural tube defects with maternal alterations and genetic polymorphisms in one-carbon metabolic pathway - Chun-Quan Cai; Yu-Lian Fang; Jian-Bo Shu; Lin-Sheng Zhao; Rui-Ping Zhang; Li-Rong Cao; Yi-Zheng Wang; Xiu-Fang Zhi; Hua-Lei Cui; Ou-Yan Shi; Wei Liu (BMC, 2019)
Abstract Background Neural tube defects (NTDs) are birth defects of the brain, spine, or spinal cord invoked by the insufficient intake of folic acid in the early stages of pregnancy and have a complex etiology involving both genetic and environmental factors. So the study aimed to explore the association between alterations in maternal one-carbon metabolism and NTDs in the offspring. Methods We conducted a case-control study to get a deeper insight into this association, as well as into the role of genetic polymorphisms. Plasma concentrations of folate, homocysteine (Hcy), S-adenosylmethionine (SAM), S-adenosylhomocysteine (SAH) and genotypes and alleles distributions of 52 SNPs in 8 genes were compared for 61 women with NTDs-affected offspring and 61 women with healthy ones. Results There were significant differences between groups with regard to plasma folate, SAM, SAH and SAM/SAH levels. Logistic regression results revealed a significant association between maternal plasma folate level and risk of NTDs in the offspring. For MTHFD1 rs2236225 polymorphism, mothers having GA genotype and A allele exhibited an increased risk of NTDs in the offspring (OR = 2.600, 95%CI: 1.227-5.529; OR = 1.847, 95%CI: 1.047-3.259). For MTHFR rs1801133 polymorphism, mothers having TT and CT genotypes were more likely to affect NTDs in the offspring (OR = 4.105, 95%CI: 1.271-13.258; OR = 3.333, 95%CI: 1.068-10.400). Moreover, mothers carrying T allele had a higher risk of NTDs in the offspring (OR = 1.798, 95%CI: 1.070-3.021). For MTRR rs1801394 polymorphism, the frequency of G allele was significantly higher in cases than in controls (OR = 1.763, 95%CI: 1.023-3.036). Mothers with NTDs-affected children had higher AG genotype in RFC1 rs1051226 polymorphism than controls, manifesting an increased risk for NTDs (OR = 3.923, 95%CI: 1.361-11.308). Conclusion Folic acid deficiency, MTHFD1 rs2236225, MTHFR rs1801133, MTRR rs1801349 and RFC1 rs1051226 polymorphisms may be maternal risk factors of NTDs.